Genetic, clinical and imaging implications of a noncompaction phenotype population with preserved ejection fraction - Grebur, Kinga; Mester, Balázs; Fekete, Bálint András; Kiss, Anna Réka; Gregor, Zsófia; Horváth, Márton; Farkas-Sütő, Kristóf; Csonka, Katalin; Bödör, Csaba; Merkely, Béla; Vágó, Hajnalka; Szűcs, Andrea (Frontiers in Cardiovascular Medicine, 2024)
Introduction The genotype of symptomatic left ventricular noncompaction phenotype (LVNC) subjects with preserved left ventricular ejection fraction (LVEF) and its effect on clinical presentation are less well studied. We aimed to characterize the genetic, cardiac magnetic resonance (CMR) and clinical background, and genotype-phenotype relationship in LVNC with preserved LVEF. Methods We included 54 symptomatic LVNC individuals (LVEF: 65±5%) whose samples were analyzed with a 174-gene next-generation sequencing panel and 54 control (C) subjects. The results were evaluated using the criteria of the American College of Medical Genetics and Genomics. Medical data suggesting a higher risk of cardiovascular complications were considered “red flags”. Results Of the LVNC population, 24% carried pathogenic or likely pathogenic (P) mutations; 56% carried variants of uncertain significance (VUS); and 20% were free from cardiomyopathy-related mutations. Regarding the CMR parameters, the LVNC and C groups differed significantly, while the three genetic subgroups were comparable. We found a significant relationship between red flags and genotype; furthermore, the number of red flags in a single subject differed significantly among the genetic subgroups (p=0.002) and correlated with the genotype (r=0.457, p=0.01). In 6 out of 7 LVNC subjects diagnosed in childhood, P or VUS mutations were found. Discussion The large number of P mutations and the association between red flags and genotype underline the importance of genetic-assisted risk stratification in symptomatic LVNC with preserved LVEF.